Cytoprotective metal-organic frameworks for anaerobic bacteria - Ji, Zhe; Zhang, Hao; Liu, Hao; Yaghi, Omar M.; Yang, Peidong (Proceedings of the National Academy of Sciences - PNAS, 2018)
We report a strategy to uniformly wrap Morella thermoacetica bacteria with a metal-organic framework (MOF) monolayer of nanometer thickness for cytoprotection in artificial photosynthesis. The catalytic activity of the MOF enclosure toward decomposition of reactive oxygen species (ROS) reduces the death of strictly anaerobic bacteria by fivefold in the presence of 21% O₂, and enables the cytoprotected bacteria to continuously produce acetate from CO₂ fixation under oxidative stress. The high definition of the MOF–bacteria interface involving direct bonding between phosphate units on the cell surface and zirconium clusters on MOF monolayer, provides for enhancement of life throughout reproduction. The dynamic nature of the MOF wrapping allows for cell elongation and separation, including spontaneous covering of the newly grown cell surface. The open-metal sites on the zirconium clusters lead to 600 times more efficient ROS decomposition compared with zirconia nanoparticles.